GE_GERICHTE P/10729/2022 vom 25. August 2025 - GE Cour de justice (2025)
AGRESSION;CHANTAGE;BRIGANDAGE;CONTRAINTE(DROIT PÉNAL);VIOLATION DES RÈGLES DE LA CIRCULATION;COAUTEUR(DROIT PÉNAL);ÉTAT DE NÉCESSITÉ | CP.134; CP.156.al3; CP.181; CP.18; CP.17; LCR.90